Pesticides in Court: Ruling on the use of neonicotinoids in EU Member States (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
In the last decades, neonicotinoid pesticides linked with bee decline have become a bone of contention in EU Member States. On the one hand, regulatory science provided by the European Food Safety Authority has been used in the interpretations established by the Court of Justice of the EU as regards the Commission’s ban of some neonicotinoids. On the other, scientific uncertainty pertaining to these chemicals underpinned the adoption of emergency measures at the national level for restricted use of the pesticides concerned. Through the line of reasoning followed by the Court’s rulings on the matter, this contribution illustrates the legal implications arising from relying on regulatory science as knowledge base that justifies both the legal invocation of the precautionary principle and the review of derogations at the national level.
Keywords: Neonicotinoids; regulatory science; pesticides regulation; precautionary principle; transparency